PROGRAM KARTU INDONESIA SEHAT (KIS) DI KABUPATEN BOLAANG MONGONDOW (STUDI DI DESA KOPANDAKAN II KECAMATAN LOLAYAN) - TABILANTANG, ASTIWARA IRFININTA; ROMPAS, WELSON; DENGO, SALMIN (Sam Ratulangi University, 2018)
As a program of the government, Kartu Indonesia Sehat is a government aid for the poor / poor, hoping toimprove the welfare of the community. Healthy Indonesia Program is a priority program of the President ofthe Republic of Indonesia Ir. Joko Widodo designed specifically to help the poor in order to get free medicalassistance. This research uses qualitative approach method. The research informants were: one head ofBPJS office, two BPJS office staff, one Kopandakan II village head, and four healthy Indonesian cardusers. Data collection by observation (direct observation), interview, and documentation, while theanalytical technique used is interactive model analysis from Miles and Huberman. Based on the researchresults can be concluded: (1) implementation of healthy Indonesian card program less effective seen fromthe dimension of communication. Socialization on matters related to the KIS program is carried out by theimplementing program (BPJS) to the community through cooperation with the village government, so thatthe public lack understanding. (2) implementation of healthy Indonesian card program is less effective, seenfrom human resource dimension of KIS program implementer from BPJS and health facility inadequate inquantity. Financial resources for program implementation are provided as needed. (3) implementation ofhealthy Indonesian card program is less effective seen from within dimension of disposition. The dispositionor characteristic of the officer does not have a consistent and consistent attitude to implement a healthy andsuccessful Indonesian card program. (4) the implementation of healthy Indonesian card program is lesseffective than the bureaucratic / organizational structure seen from the mechanism and procedure ofprogram implementation (SOP) which determined the lack of person in handling the program. Duties andresponsibilities are clearly defined. As for the suggestion: (1) socialization of healthy Indonesian cards tothe village community needs to be continuously improved and intensified because many villagers do notunderstand clearly the healthy Indonesia card program. (2) the implementing resources of healthyIndonesian card program from BPJS should be increased so that more can reach to the villages. HR inhealth facilities (health workers) for KIS participant services should also be able to reach the village. (3) thedisposition (commitment and consistency) of health card program implementing officers still needs to beimproved to improve the successful implementation of the program in the future. (4) BPJS should place KISservice officers in sub-districts and villages so that they can be easily reached by the people in the villages.Keywords: Implementation, Healthy Indonesia Program, Card Indonesia Healthy